Emergency anaphylaxis protocols: A cross-sectional analysis of general practice surgeries and pharmacies in both the urban and rural setting in Ireland. (1st January 2018) - O'Brien, Hannah; Mc Conaghy, David; Brennan, Declan; Meaney, Sarah
Abstract: Background: The incidence of anaphylaxis appears to be increasing worldwide with cases in the community outnumbering those in the hospital setting. General practice (GP) surgeries and pharmacies, based in the community, are often the first point of contact for many patients suffering from anaphylaxis. Objectives: To determine if studied GP surgeries and pharmacies have an anaphylaxis protocol on site and have access to an anaphylaxis kit; to explore GP's and pharmacists' personal experiences with management of anaphylaxis. Methods: A cross-sectional, questionnaire-based study was performed examining anaphylaxis protocols in a sample of general practices and pharmacies from some counties in Ireland. This consisted of a sample from rural and urban settings. The study commenced in October 2014. Results: Nineteen of 24 GPs (79%) and 9 (29%) pharmacies had an anaphylaxis protocol ( P < 0.001). Twenty-four (100%) GP practices and 12 pharmacies (39%) surveyed had an anaphylaxis kit on site. Twelve GPs (50%) had treated a patient with anaphylaxis in the surgery while 8 (33%) had treated a patient in the community. One pharmacist (3%) had witnessed anaphylaxis in practice. Two pharmacies and one GP had been contacted by local businesses to alert them to a case of anaphylaxis. Conclusion: In contrast to national and international guidelines only 79% of GPs and 29% of pharmacies in this study from Ireland had an anaphylaxis protocol onsite.